Screening of Tomato Seed Bacterial Endophytes for Antifungal Activity Reveals Lipopeptide Producing Bacillus siamensis Strain NKIT9 as a Potential Bio-Control Agent - Sharma, Ayushi; Kaushik, Nutan; Sharma, Abhishek; Bajaj, Abhay; Rasane, Mandar; Shouche, Yogesh S.; Marzouk, Takwa; Djébali, Naceur (Frontiers in Microbiology, 2021)
The current study investigates the diversity pattern and fungicidal potential of bacterial endophytes isolated from two different organic varieties of tomato plants (V1 and V2). A total of seventy-five bacterial isolates identified by 16S rRNA gene sequencing revealed a majority of genus as Bacillus and one Planococcus, which were grouped into 8 different species. The Shannon diversity H’ (1.56), Simpson’s index of diversity (0.93), Magalef' index (2.23), Evenness (0.96), and Species richness (7) indicated the high endophytic bacterial diversity in the V1 variety of the tomato. Bacterial endophytes isolated from both the varieties were screened for their antifungal activity against five economically critical fungal pathogens (viz., Botrytis cinerea, Rhizoctonia solani, Fusarium solani, Verticillium lateritium, and Alternaria solani) of tomato crop through dual culture assay. The data revealed B. siamensis strain NKIT9 as the most potent antagonist, significantly (p<0.05) inhibiting the mycelial growth between 75 to 90% against selected fungal pathogens. High bioactivity of lipopeptide extract of strain NKIT9 was recorded against R. solani with minimum IC50 value of 230 µg/ml. The Ultra Performance Liquid Chromatography-High Definition Mass Spectrometry (UPLC-HDMS) analysis of this lipopeptide extract revealed the presence of Surfactin and Bacillomycin D. Furthermore, in-vitro results showed that the selected bacterial strain significantly minimized the disease incidence in damping-off assay which makes this strain a promising antifungal bio-control agent. Moreover, in pot experiment the NKIT9 increased the fruit yield by 59.2% compared with the untreated R. solani infested control.